"IMOOJI" UNTUK OLAHAN JANTUNG PISANG DESA MOJOGEDANG KABUPATEN KARANGANYAR - Susanti, Nani; Haryanti, Haryanti; Sapariyah, Rina Ani; Sutanto, Yusuf; Fatonah, Siti (Adi Widya : Jurnal Pengabdian Masyarakat, 2024)
Not having the geographic potential to be explored as a tourist area does not discourage the people of Mojogedang Village from improving their welfare. The objectives to be achieved in this activity are: To train Mojogedang Village PKK members to master marketing techniques through social media and internet networks by creating interesting content with digital marketing facilities so that they can generate significant income to improve the family economy in Mojogedang Village as a supporting area for Tourism Village in Mojogedang District. The approach technique is carried out using seminar methods and simulations directly utilizing the laptop and smartphone of each participant. With this dedication, Mojogedang Village PKK members can open their minds to competition, quality products, and the correct production process and develop themselves through digital marketing training, to improve economic welfare in the future. The following is the link to the results of the training https://bit.ly/Nuget_Jantungpisang_MojoGedang